Sintesis Hijau Nanopartikel TiO2 Menggunakan Ekstrak Daun Belimbing Wuluh (Averrhoa blimbi L.) dan Aktivitas Antibakterinya Terhadap Escherichia coli - Nur Azizah Wanda Triyaruhana; Dina Kartika Maharani (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2026)
TiO2 nanoparticles were successfully synthesized by biosynthesis method specifically green synthesis method using Averrhoa bilimbi L. (bilimbi) leaf extract as both a reducing and capping agent. The purpose of this study was to characterize the synthesized TiO2 nanoparticles and its antibacterial activity against the Gram-negative bacteria Escherichia coli. Characterization was carried out using Fourier-Transform Infrared Spectroscopy (FTIR) and X-Ray Powder Diffraction (XRD). The synthesized TiO2 nanoparticles exhibited an anatase phase, with an average crystallite size of 12.9 nm and a crystallinity of 97.81%. Antibacterial activity tests against Escherichia coli across various samples Ti-BW20 and Ti-BW40, yielded inhibition zone diameters of 7.82 mm and 9.87 mm, respectively.